Transform Nutrition West Africa rapid reviews: A resource bank - Verstraeten, Roosmarijn; Salm, Leah; Booth, Andrew (International Food Policy Research Institute, 2021)
Decisionmakers (including implementers, policymakers, technical agencies) require accurate and relevant evidence by which to plan, develop, and implement nutrition and health programs in a timely fashion. They need to know the effectiveness of interventions and policies, how and in what settings these interventions work, and their cost-effectiveness. Systematic reviews are increasingly used to inform decisions and produce guidance for health systems. Production of systematic reviews, however, is often protracted, resource intensive, and incompatible with decision-making timelines; they can take one to two years to complete. Rapid reviews offer an alternative, rapid and timely approach to providing actionable and relevant evidence that can be used to inform decisions about health systems in both routine and emergency contexts. Rapid reviews are generated through a transparent, scientific, and reproducible method that preserves key principles of knowledge synthesis.